2021
DOI: 10.1371/journal.pone.0254825
|View full text |Cite
|
Sign up to set email alerts
|

Perceived fear of COVID-19 and its associated factors among Nepalese older adults in eastern Nepal: A cross-sectional study

Abstract: Background Coronavirus disease 2019 (COVID-19) has affected all age groups worldwide, but older adults have been affected greatly with an increased risk of severe illness and mortality. Nepal is struggling with the COVID-19 pandemic. The normal life of older adults, one of the vulnerable populations to COVID-19 infection, has been primarily impacted. The current evidence shows that the COVID-19 virus strains are deadly, and non-compliance to standard protocols can have serious consequences, increasing fear amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
7
23
1
7
Order By: Relevance
“…Thus far, the clinical evidence reveals that both COVID‐19 mortality and fatality rates are related to older age (Han et al, 2021; Leung, 2020). This finding is in line with some recent studies indicating that older adults were more fearful of contracting COVID‐19 than young people (Gokseven et al, 2021; Mistry et al, 2021; Yadav et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, the clinical evidence reveals that both COVID‐19 mortality and fatality rates are related to older age (Han et al, 2021; Leung, 2020). This finding is in line with some recent studies indicating that older adults were more fearful of contracting COVID‐19 than young people (Gokseven et al, 2021; Mistry et al, 2021; Yadav et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…20 Our findings concur with the study of Troisi et al, who reported a positive relationship between age and fear level among the health-care personnel of Italy, and the study of Yadav et al which also reported a greater level of COVID-19 fear among the Nepalese older adults. 21,22 Male gender in our study showed a more significant psychological impact. Male participants in our study were found to have significantly altered levels of all four psychological distress parameters assessed in this study compared to their female counterparts.…”
Section: Discussionmentioning
confidence: 49%
“…Since COVID-19 and the highest mortality and complication rate were found in elderly subjects during the outbreak, it is not surprising that older CV patients are more likely to be psychologically affected, as reported in several general populations [23][24][25][26][27]. However, some studies reported lower levels of COVID-19 fear in older subjects than in young to middle-aged adults [21].…”
Section: Discussionmentioning
confidence: 88%